2022
DOI: 10.3389/fsurg.2022.817134
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy vs. Laparotomy for the Management of Abdominal Trauma: A Systematic Review and Meta-Analysis

Abstract: BackgroundThere is still no consensus regarding the role of laparoscopy in trauma cases. The purpose of this paper is to assess the value of diagnostic and therapeutic laparoscopy for patients with blunt or penetrating abdominal trauma by performing a systematic review and meta-analysis.MethodsPubMed, Embase, and the Cochrane library were systemically searched for the randomized controlled trials (RCTs) and non-RCT comparative studies on effectiveness and safety of laparoscopy vs. laparotomy for the two author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
0
15
0
5
Order By: Relevance
“…Case Reports in Surgery triple contrast CT scan [4]. This is not always available in all resource The standard management protocol for penetrating inal trauma is laparotomy [5,15]. However, management of patients poses a dilemma for attending trauma surgeons weighing the risk of missing life threating injuries when non/ minimal invasive diagnostic and therapeutic procedures are opted versus the standard traditional open laparotomy method [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Case Reports in Surgery triple contrast CT scan [4]. This is not always available in all resource The standard management protocol for penetrating inal trauma is laparotomy [5,15]. However, management of patients poses a dilemma for attending trauma surgeons weighing the risk of missing life threating injuries when non/ minimal invasive diagnostic and therapeutic procedures are opted versus the standard traditional open laparotomy method [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy on the roles of diagnostic laparoscopy in management of penetrating abdominal injuries [ 20 ] with no consensus on its role [ 15 ] The high rate of missed injuries and development of tension-pneumothorax pose a serious risk in trauma patients [ 16 ]. Patients with haemodynamic instability, intracranial trauma, bowel evisceration, and overt peritonitis are contraindicated for laparoscopy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopy is superior to laparotomy in terms of reduction of postoperative pain, length of hospital stay, surgical site infections and peritoneal adhesions [4] , [5] . A study comparing the two approaches for the treatment of hollow viscus injuries in abdominal trauma, on nearly 4000 patients, concluded that laparoscopy was superior in terms of postoperative complications [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Wang considered that laparoscopic surgery can be a practical alternative to laparotomy for appropriate patients. Decisions to perform laparoscopy should be based on the experiences of the surgeon and the resources available [ 23 ]. Kones et al [ 4 ] identified two indications for the choice of laparotomy for thoracoabdominal injuries – hemodynamic instability and peritonitis.…”
Section: Special and Non-specialized Diagnostic Methodsmentioning
confidence: 99%